The New Health-Related Top-Level Domains Are Coming: Will Cureforcancer.health Go to the Highest Bidder? - Eysenbach, Gunther (JMIR Publications, 2014)
In 2012, the Internet Corporation for Assigned Names and Numbers (ICANN) opened a new round of applications for generic top-level domain (gTLD) names, receiving 1930 applications, of which at least 18 were related to health (eg, ".doctor", ".health", ".med"). The entry of new, commercial players applying to create health-related names reopens the debate on the role of international organizations, governments, non-governmental organizations, and other stakeholders regarding the safeguards and policies needed to protect consumers.